Risk Management in Organizations in Bulgaria – Issues and Prospects for Development - Tsvetkov, Tsvetan (Research Papers, 2022)
The current state of the risk environment in the organizations in Bulgaria is analyzed in order to establish the good practices and the available problems. The complex analysis of the risk environment in the country is difficult since the risks have many dimensions, the concept of risk is an interdisciplinary category, the threats and sources of risk that underlie the various risks are also very diverse.Many international organizations publish their research on the most significant risks to the world in the short, medium, and long term – the World Economic Forum, INFORM and the Interagency Reference Group of the Standing Committee on Risk, Early Warning and Preparedness and many others.The identification of the issues in risk management in the Bulgarian organizations is based on an analysis of numerous literature sources, the author’s personal experience and conversations with persons directly involved in risk management.Prospects for the development of risk management practice in Bulgarian organizations are systematized in the following areas: introduction of risk management standards, adoption of a systematic approach to risk management, development and implementation of a model for assessing the maturity of risk management in organizations, application of contemporary methods for risk identification and analysis, which have proven their effectiveness, but are still not sufficiently applied in the practice of Bulgarian organizations.
Keywords: Risk management; Sources of risk; Risk management standards; Risk